Cord blood 25-hydroxy Vitamin D and Fluoride in newborn with congenital anomalies - Ghosh, Abhra; Bhardwaj, Jagriti (Asian Journal of Medical Sciences, 2020)
Background: It is well known that deficiency of 25 - hydroxy Vitamin D can cause various musculoskeletal manifestations as well as metabolic, non-musculoskeletal abnormalities. There may be a chance that hypovitaminosis D can act as a causative factor for congenital anomalies. Aims and Objectives: The present study was planned to evaluate the level of 25 - hydroxy Vitamin D in cord blood in cases of congenital anomalies and its association with cord blood fluoride levels in newborns with visible congenital anomalies. Materials and Methods: Thirty newborns with visible congenital anomalies were included in group I and thirty healthy newborns without any congenital anomalies were included group II. Ten mL cord blood was collected from the placental end of umbilical cord immediately after delivery of the baby and serum was separated. Serum 25 - hydroxy Vitamin D and fluoride were analyzed by standard methods. Statistical analysis: Results were expressed as Mean ± SD. Unpaired ‘t’ test and Pearson correlation test were applied. Data were considered to be significant if p < 0.05. Results: Serum 25 - hydroxy Vitamin D levels were significantly decreased in babies with congenital anomalies (p=0.001) and show a significant negative association with fluoride.Anomalies related to central nervous system and musculoskeletal systems had the lowest 25 - hydroxy Vitamin D levels and highest serum fluoride levels than other anomalies of other systems. Conclusion: Fluoride can acts as an inhibitor for activation of calciferol causing a decrease in 25 - hydroxy Vitamin D levels. Thus 25 - hydroxy Vitamin D is an important micronutrient for proper development of the fetus and association of it with excess fluoride can cause congenital anomalies.